Loss of Hsp70 in Drosophila is pleiotropic, with effects on thermotolerance, recovery from heat shock and neurodegeneration. - Gong, W.J.; Golic, K.G. (Genetics, 2006)
The heat-shock response is a programmed change in gene expression carried out by cells in response to environmental stress, such as heat. This response is universal and is characterized by the synthesis of a small group of conserved protein chaperones. In Drosophila melanogaster the Hsp70 chaperone dominates the profile of protein synthesis during the heat-shock response. We recently generated precise deletion alleles of the Hsp70 genes of D. melanogaster and have used those alleles to characterize the phenotypes of Hsp70-deficient flies. Flies with Hsp70 deletions have reduced thermotolerance. We find that Hsp70 is essential to survive a severe heat shock, but is not required to survive a milder heat shock, indicating that a significant degree of thermotolerance remains in the absence of Hsp70. However, flies without Hsp70 have a lengthened heat-shock response and an extended developmental delay after a non-lethal heat shock, indicating Hsp70 has an important role in recovery from stress, even at lower temperatures. Lack of Hsp70 also confers enhanced sensitivity to a temperature-sensitive lethal mutation and to the neurodegenerative effects produced by expression of a human polyglutamine disease protein.